2014
DOI: 10.3928/00220124-20140925-15
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Job Satisfaction of New Graduate Nurses Participating in Nurse Residency Programs: A Systematic Review

Abstract: Nurse residency programs are designed to increase competence and skill, and ease the transition from student to new graduate nurse. These programs also offer the possibility to positively influence the job satisfaction of new graduate nurses, which could decrease poor nursing outcomes. However, little is known about the impact of participation in a nurse residency program on new graduate nurses’ satisfaction. This review examines factors that influence job satisfaction of nurse residency program participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 35 publications
5
63
0
1
Order By: Relevance
“…We found several reviews of factors related to nurses’ job satisfaction carried out over the past 20 years (Hayes et al, ; Li et al, ; Lin, Viscardi, & McHugh, ; Lu et al, ; Lu, While, & Louise Barriball, ; Maqbali, ; Utriainen & KyngÄS, ). However, there has been no systematic assessment of the differences and similarities between job satisfaction for nurses practicing in acute care settings in rural and urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…We found several reviews of factors related to nurses’ job satisfaction carried out over the past 20 years (Hayes et al, ; Li et al, ; Lin, Viscardi, & McHugh, ; Lu et al, ; Lu, While, & Louise Barriball, ; Maqbali, ; Utriainen & KyngÄS, ). However, there has been no systematic assessment of the differences and similarities between job satisfaction for nurses practicing in acute care settings in rural and urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…A review of new graduates (Lin, Viscardi, & McHugh, ) reported that support, camaraderie and positive relations with staff led to job satisfaction…”
Section: Introductionmentioning
confidence: 99%
“…A review of strategies to enhance novice nurses’ retention indicated the use of a clinical preceptor programme of some kind (Lin et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Harrison & Ledbetter ; Kram & Wilson ; Letourneau & Fater ; Lin et al. ; Rosenfeld & Glassman ; Trepanier et al. ); reduce stress and anxiety (Edwards et al.…”
Section: Introductionmentioning
confidence: 99%